Commitment And Renewal As Mediators In The Relationship Between Catechnical Participation And Facilitator Competence Towards The Effectiveness Of Catechism Of The People - Sugiyana Sugiyana; Nerita Setiyaningtiyas; Timotius Tote Jelahu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Effectiveness catechesis people are greatly influenced by involvement and competence facilitator catechesis as agent main in news faith. However, the effectiveness This No only depends on participation and competence only , but also in existence strong commitment and renewal in approach catechesis . Research This aiming For test role commitment and renewal as a mediator in connection between participation catechesis and competence facilitator to effectiveness catechesis people. Research This use approachquantitative descriptive with design survey. Data collected from 73 respondents guide catechesis in some the selected parish by purposive sampling. Data collection was carried out through questionnaire structured. Data analysis using method statistics path analysis for test influence direct and indirect direct participation catechesis (X1) and competence facilitator (X2) against effectiveness catechesis people (Y) with commitment and renewal catechesis (Z) as mediator variable. Research results show that participation catechesis (X1) and competence facilitator (X2) has influence significant direct to effectiveness catechesis people (Y). In addition, it was found that commitment and renewal catechesis (Z) mediates in a way significant connection between X1 and X2 on Y. No influence direct through this mediator strengthens the relationship between variable independent and dependent, which indicates importance updates and commitments in implementation catechesis. Findings This confirm that besides activity and competence facilitator, strong commitment and innovation in Updates method catechesis is element important in increase effectiveness catechesis people. Commitment strengthens motivation facilitator, while Updates ensure relevance catechesis with needs people today. Research This recommend training program development facilitator who does not only focus on competence technical but also build commitment and creativity in pastoral renewal.